PERANCANGAN PENGUKURAN KINERJA PADA PT JAYA CELCON PRIMA DENGAN METODE PERFORMANCE PRISM DAN SCORING OMAX (OBJECTIVES MATRIX) - Laricha, Lithrone; Agusman, Delvis; Agrida, Sanvy (Teknik dan Ilmu Komputer, 2012)
Celcon blocks produced by PT Celcon Jaya Prima are more commonly used in multistorey buildings such as offices, hospitals, hotels, industries, rather than in residential housing. To increase the stakeholdersâ satisfaction and to be more competitive, PT Celcon Jaya Prima needs to develop further its products, one of which is by measuring the companyâ performance. Performance measurement is done by determining the variables of KPI (Key Performance Indicator) by using Performance Prism method including stakeholder satisfaction, strategies, processes, capabilities, and stakeholdersâ contributions. KPI calculation was done by AHP method. Performance measurement was performed by OMAX scoring after the weighting process completed. The results showed that PT Celcon Jaya Prima did not meet three of the KPIâs targets. It is proposed that the company employs KPI Process 5 as a way to expand its marketing strategy. Â Keywords: celcon block, performance prism, KPI, AHP, OMAX